A Galois Correspondence for Reduced Crossed Products of Simple C^* -algebras by Discrete Groups. (October 2019) - Cameron, Jan; Smith, Roger R.
Abstract: Let a discrete group G act on a unital simple C^* -algebra A by outer automorphisms. We establish a Galois correspondence HA times _[STIX]x1D6FC, rH between subgroups of G and C^* -algebras B satisfying ABA times _[STIX]x1D6FC, rG, where A times _[STIX]x1D6FC, rG denotes the reduced crossed product. For a twisted dynamical system (A, G, [STIX]x1D6FC, [STIX]x1D70E), we also prove the corresponding result for the reduced twisted crossed product A times _[STIX]x1D6FC, r^[STIX]x1D70EG .